Measurement of urine output by weighing nappies. Issue 2 (1st March 2004) - Oddie, S; Adappa, R; Wyllie, J
Abstract : The effect of humidity on measurement of neonatal urine output was assessed by weighing nappies in a clinically relevant context. Saline was used as dummy urine, on modern nappies in incubators at various humidity settings. In at least some additional humidity, no clinically relevant evaporative loss occurred.